The evolution of the parliamentary apparatus in Ukraine. - Погребняк, Н. С. (Theory and practice of jurisprudence, 2016)
The basic stages, features and problems of the evolution of the Apparatus of the Parliament in Ukraine have been investigated in the article. The trends and patterns of changes of it status on different stages of the development were identified. The conclusion was made about the permanent process of the improvements of the Apparatus in the direction of institutional and functional expansion.